2018
DOI: 10.1111/hae.13410
|View full text |Cite
|
Sign up to set email alerts
|

A prospective surveillance study of inhibitor development in haemophilia A patients following a population switch to a third‐generation B‐domain‐deleted recombinant factor VIII

Abstract: Our surveillance study shows comparable inhibitor development to similar published studies. A significant increase in FVIII utilization was noted for the whole cohort, switchers and non-switchers. Lastly, no clinically significant changes were observed in ABR for joint bleeds, but a difference for non-joint bleed ABRs was observed in switchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…18 Moreover, after switching to Refacto AF from other products than Kovaltry R , often inhibitors have been found: in a non-random comparison from the United Kingdom, a not statistically significant (P = .06) difference in inhibitor incidence between switchers to Refacto AF R (7.8 per 1000 treatment years) and non-switchers (1.5 per 1000 years; IRR 5.3, 95% CI 0.5-260.3) was reported 19 and in a Canadian surveillance two inhibitors among 125 switchers to Refacto AF R were found. 20 If, indeed, Kovaltry R is relatively less and Refacto AF R relatively more immunogenic this difference might explain (in part) the occurrence of inhibitors in our patients. Considering that antigen persistence for immunologic unresponsiveness is a necessity, 21,22 Kovaltry R may have caused loss of tolerance to exogenous FVIII, especially in our young patients because of less long and less variable exposition to (different) FVIII products than older patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…18 Moreover, after switching to Refacto AF from other products than Kovaltry R , often inhibitors have been found: in a non-random comparison from the United Kingdom, a not statistically significant (P = .06) difference in inhibitor incidence between switchers to Refacto AF R (7.8 per 1000 treatment years) and non-switchers (1.5 per 1000 years; IRR 5.3, 95% CI 0.5-260.3) was reported 19 and in a Canadian surveillance two inhibitors among 125 switchers to Refacto AF R were found. 20 If, indeed, Kovaltry R is relatively less and Refacto AF R relatively more immunogenic this difference might explain (in part) the occurrence of inhibitors in our patients. Considering that antigen persistence for immunologic unresponsiveness is a necessity, 21,22 Kovaltry R may have caused loss of tolerance to exogenous FVIII, especially in our young patients because of less long and less variable exposition to (different) FVIII products than older patients.…”
Section: Discussionmentioning
confidence: 76%
“… 18 Moreover, after switching to Refacto AF from other products than Kovaltry R , often inhibitors have been found: in a non-random comparison from the United Kingdom, a not statistically significant ( P = .06) difference in inhibitor incidence between switchers to Refacto AF R (7.8 per 1000 treatment years) and non-switchers (1.5 per 1000 years; IRR 5.3, 95% CI 0.5-260.3) was reported 19 and in a Canadian surveillance two inhibitors among 125 switchers to Refacto AF R were found. 20 …”
Section: Discussionmentioning
confidence: 99%
“…49 Although no major concerns exist for patients who switched from other FVIII products, lifelong surveillance for inhibitor development is recommended in all previously tolerised patients irrespective of factor concentrate used. 50 Finally, some observational studies and case reports have investigated the outcomes of using rFVIIIFc in patients with haemophilia A undergoing major surgery. [51][52][53][54][55][56][57] The authors reported that rFVIIIFc provided effective haemostasis in major surgery without significant bleeding; data are summarised in Table 3.…”
Section: Rf Viiifc In Clini C Al Pr Ac Ticementioning
confidence: 99%
“…In addition, emerging data on the use of rFVIIIFc in patients previously tolerised on another FVIII product showed no recurrence of inhibitor after switch to rFVIIIFc 49 . Although no major concerns exist for patients who switched from other FVIII products, lifelong surveillance for inhibitor development is recommended in all previously tolerised patients irrespective of factor concentrate used 50 …”
Section: Rfviiifc In Clinical Practicementioning
confidence: 99%
“…22 Additionally, stud ies indi cate no increased risk of inhibi tor devel op ment when switching to another type or brand of fac tor. 29,30 Whether to use plasma-derived vs recom bi nant fac tor con cen trates is a mat ter of dealer's choice. Practically, regional avail abil ity and pay ers (gov ern ment or insur ance com pa nies) pref er ence due to nego ti ated pro cure ment discounts (as well as out-of-pocket cost for US patients) play a larger role in deter min ing the spe cific prod uct of CFC to prescribe within each type.…”
Section: Types Of Fac Tor Con Cen Tratesmentioning
confidence: 99%